(3eaJGM GdMceIs - (3CHhYHO Gddg eMeO Hf Cejd Hf YHO Gddg Hf Cejd Hf eMeO GdJejejs
(3ChdgG (B:s
( (3heG Hce ef fYeI aef Gddg Ke EPG eSce GdVQ aEdjg hGJbhG Gddg hjYdece Gddg hGddg Hcd TF Ydje (B) (3hHYO agPG cJGH CPcQ ajg SQ JQcjH GdCLQGe GdYdhjI hGdSadjI s
(3BNQgG (B:s
(3hgh GdJOGHjQ GdPi MGQJ ajg GdMceGA JOHjQ GdadGSaI hLejY eG jMJGL Edjg HGWfg ef LejY GdCbSGe GdKdGKI hUGQ JeGekG CHO GdBHOjf hOgQ GdOGgQjf hGddg SHMGfg hJYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs